The Social Work Degree Apprenticeship - Stone, Clare; Shannon, Mary (Critical Publishing, 2022)
Developed specifically for the social work degree apprenticeship, this book guides apprentices through the unique requirements of this new qualifying route. With contributions from academics, employers and students, it provides a broad and inclusive perspective to build effective working relationships.   The social work degree apprenticeship is unlike any other qualifying route to become a professional social worker. Apprentices have to juggling a number of competing demands, balancing their work and learning commitments, the expectations of their employer and those of their university. It can be intense, high-paced and stressful, and very often apprentices are mature students who may not have been in formal learning environment for many years.  This book has been written specifically with apprentices in mind and by a range of stakeholders, not just academics, who draw upon their experience and expertise to help apprentices successfully navigate this qualification. Key theoretical concepts are introduced throughout, practical advice given and learning features encourage reflection and application, making this a go-to textbook, whether it's your first time taking a degree or you're a mature student returning to study - this is an essential companion to your learning journey, helping you manage your relationship with your university and employer.